(untitled) (Global Journal of Human-Social Science, 2021)
The literature indicates that conflict can result in food insecurity due to economic or political crisis. However, few studies have investigated the effects that nonviolent interstate conflict has on food security in the Middle East. Evidence from this study, based in Qatar, indicates that conflict can result in food insecurity due to economic or political crisis. This research critically examines the lingering political and economic blockade of the State of Qatar and the extent to which this blockade has impacted food security of residents. The study employed a sequential mixed methods approach to gain better insight into the nature of food security in Qatar. A focused qualitative review of the relevant literature was followed by a quantitative analysis which revealed that there was no significant effect of interstate conflict on food security, while the economic and political blockade correlated significantly with food security. Three groups were sampled, including government officials, regulatory agencies, and food suppliers.